Preparation of Chitosan Coated Magnetic Hydroxyapatite Nanoparticles and Application for Adsorption of Reactive Blue 19 and Ni2+ Ions. (30th January 2014) - Nguyen, Van Cuong; Pho, Quoc Hue
Abstract : An adsorbent called chitosan coated magnetic hydroxyapatite nanoparticles (CS-MHAP) was prepared with the purpose of improvement for the removal of Ni 2+ ions and textile dye by coprecipitation. Structure and properties of CS-MHAP were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and vibrating sample magnetometer (VSM). Weight percent of chitosan was investigated by thermal gravimetric analysis (TGA). The prepared CS-MHAP presents a significant improvement on the removal efficiency of Ni 2+ ions and reactive blue 19 dye (RB19) in comparison with chitosan and magnetic hydroxyapatite nanoparticles. Moreover, the adsorption capacities were affected by several parameters such as contact time, initial concentration, adsorbent dosage, and initial pH. Interestingly, the prepared adsorbent could be easily recycled from an aqueous solution by an external magnet and reused for adsorption with high removal efficiency.